2017
DOI: 10.1007/s00204-017-2084-9
|View full text |Cite
|
Sign up to set email alerts
|

ROS generation and JNK activation contribute to 4-methoxy-TEMPO-induced cytotoxicity, autophagy, and DNA damage in HepG2 cells

Abstract: 4-Methoxy-TEMPO, a derivative of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), is a stable nitroxide radical and is generally used in organic and pharmaceutical syntheses for the oxidation of alcohols. Previously, we reported the involvement of reactive oxygen species (ROS) and c-Jun N-terminal kinases (JNK) in TEMPO-induced apoptosis in mouse L5178Y cells. In this study, we investigated 4-methoxy-TEMPO induced toxicity in human HepG2 hepatoma cells and its underlying mechanisms. Treatments with 4-methoxy-TEMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 50 publications
5
38
1
Order By: Relevance
“…JNK are extremely important in the process of apoptotic cell death as one subgroup of the MAPK family. JNK and ERK, as stress‐activated protein kinases, are activated by various stress stimuli, such as bioactive compounds, to induce apoptosis . Consistent with these results, we observed that JNK activation and ERK1/2 activation were involved in RA‐induced apoptosis in a drug concentration‐ and time‐dependent method.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…JNK are extremely important in the process of apoptotic cell death as one subgroup of the MAPK family. JNK and ERK, as stress‐activated protein kinases, are activated by various stress stimuli, such as bioactive compounds, to induce apoptosis . Consistent with these results, we observed that JNK activation and ERK1/2 activation were involved in RA‐induced apoptosis in a drug concentration‐ and time‐dependent method.…”
Section: Discussionsupporting
confidence: 88%
“…As a heterogeneous group of diatomic oxygen molecules from free and nonfree radical species, ROS trigger apoptosis by causing various cellular stresses and regulate several apoptotic effectors, such as caspases, Bcl‐2, and cytochrome c . Broadly speaking, ROS are capable of activating p38 MAPK, JNK, ERK, and Akt pathways, depending on the context …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of MAPKs, especially the stress-activated kinase, JNK, is common under conditions of oxidative stress. In most cases, MAPK activation occurs downstream of ROS generation [81,82]; however, activated MAPKs can also positively regulate ROS generation in certain conditions [44,83], (Huo et al 2016).…”
Section: P53 Exerts Antioxidant Activity By Inhibiting C-jun N-mentioning
confidence: 99%
“…4-Methoxy-2,2,6,6-tetramethylpiperidine 1-oxyl, shortened to MetT, is a stable cyclic nitroxide derivative based on TEMPO, with a substitution at position 4 for a methoxy group [15]. The complete characterisation of the functional difference of this substitution to other nitroxides is lacking in the literature, but MetT appears to have similar activity to other cyclic nitroxides [16].…”
Section: Introductionmentioning
confidence: 99%